The Teaching of The Speaking Skill Using The Audio-Oral Method for The Students of Islamic Senior High School of Zainul Hasan Genggong Probolinggo - Edi Kurniawan Farid; Mamluatun Ni'mah; Nur Arifah (Mantiqu Tayr: Journal of Arabic Language, 2021)
This research aims to know the teaching of the speaking skill using the audio-oral method for the students of Islmic Senior High School of Zainul Hasan Genggong Probolinggo and to know its problems. This qualitative research used observation, interview, and documentation to collect data. To analyze the data, this research based on three basic things, data reduction, data presentation, and extrapolation. And, to measure the validity of the data, this research used triangulation. The results of this research are the teaching of the speaking skill using the audio-oral method for the students of Islmic Senior High School of Zainul Hasan Genggong Probolinggo by giving the dialogues, then translates them and represents the pronunciation in the Arabic dialect, which the students hear and then imitate afterwards sometimes the tape recorder used for improving the arabic speaking skill correctly while teaching continued with more exercises in various Arabic dialogues. The problems of the teaching of the speaking skill using the audio-oral method for the students of Islmic Senior High School of Zainul Hasan Genggong Probolinggo consist of three basic problems which are related to the language environment, the local language, the monotonic teaching method and learning media.